O método Let Us play na maximização da atividade física em crianças - Silva, Igor Joaquim Oliveira (2020)
Most children and adolescents don’t reach the recommended levels of physical activity. Given the positive impacts of Physical Education on physical activity levels in this age group, strategies to improve the moments directed to the promotion of physical activity, may be relevant in contributing to increasing opportunities for practice and consequently increasing the levels of daily physical activity of this population. In order to meet these needs, the LET US PLAY strategy was developed in the United States, aiming to maximize the uptime of children and teenagers during traditional games and play. Considering the positive impact of actions on physical activity as well as the Brazilian reality, this study aimed to compare the number of steps, intensity and satisfaction of children, between 08 and 12 years, during games and games modified, according to the principles of LET US PLAY, versus the same activities played in traditional rules. The study included 25 students between 08 and 12 years old, of both sexes (11 boys and 14 girls), enrolled in an EMEB in the municipality of Cuiabá-MT. Participants were monitored by the Mi Band 2 smart bracelet, fixed on the left wrist during 10 physical education classes with 50 minutes of duration, divided into two moments of 15 minutes with 10 minute interval for water and 5 start/end heating and stretching. Descriptive and comparative analyses were used by means of mean, standard deviation and percentage. Tukey’s post hoc ANOVA test was used to analyze the difference in the number of steps between strategies, considering the order of interventions and the gender of the children and the Chi-square to verify the prevalence in satisfaction and perceived effort, the significance level of 5% was adopted. It was observed that the total number of steps taken by children in the LET US PLAY intervention was higher than the traditional (1515±825 vs 957±507; p<0.05), both in boys (1795±1020 vs 1110±598; p<0.05) and girls (1318±581 vs 851±403), regardless of the order of application, in all games with emphasis on burned for boys and futsal for girls. The levels of satisfaction and perceived effort between the methodologies showed no significant difference (p>0.05). It is concluded that modifying the rules of traditional games and games using the principles of the LET US PLAY strategy increases the time in physical activity of children and adolescents during school physical education classes. Besides, generate positive satisfaction and perception of effort similar to that of games in their traditional format.